MEMENANGI PERSAINGAN PPDB DENGAN MENINGKATKAN KUALITAS SEKOLAH DAN MEMANFAATKAN MEDIA SOSIAL - Wakhudin Wakhudin; Beny Wijarnako; Cahyono Purbomartono (Ekalaya: Jurnal Pengabdian Kepada Masyarakat Indonesia, 2023)
Admission of New Students (PPDB) in primary and secondary education units continues to experience dynamics. Contestation among schools, especially non-favorites, in getting new students is often colored by gratification. In order to apply to the school, the school provides a stimulus by providing uniforms, shoes, bags, stationery and so on. This mode is the most basic gratification exercise. In fact, Permendikbud No. 1 of 2021 concerning the Admission of New Students (PPDB) Chapter II concerning Procedures for Accepting New Students Article 2 paragraph (1) states, PPDB is implemented objectively, transparently, and accountably. Education units have many options in marketing education, avoiding a variety of commendable action options. The best option is to improve the quality of educational services starting from the management of marketing services. The quality of RATER services (reliability, assurance, tangible, empathy, and responsiveness) is expected to be a solution to the increasingly tough competition in PPDB, especially when the world community enters the era of industrial revolution 4.0. Among educational marketing management, social media-based educational marketing is the hottest option. Because, social media today is increasingly dominant to be a part of the lives of all generations, from the older, middle generation, let alone the millennial generation.  The best improvement of educational services is to improve the quality of educators. Teachers are the key role in whether or not education services are qualified. No matter how good the curriculum is, if the educator's services in the education unit are of low quality, then the education services remain low. On the contrary, no matter how bad the curriculum is, if the teachers who teach are of high quality, then the quality of educational services is high. Ideally, the best educational services start from a quality concept, are implemented by qualified educators, and are managed using services that are reliable, guaranteed, real, empathetic, and responsive to various phenomena that occur, especially for students. Quality educators who are managed with school-based management that is also qualified make the school an ideal place for learning for students. This kind of education unit is what parents are looking for to entrust their children to study at school. By improving the quality of schools plus a social media-based marketing system, it is the best way to win the competition for the admission of new students elegantly